Tradisi Tabuik, Warisan Islam dan Budaya Lokal Pariaman - Faisyal, Faisyal; Priyatna, Yana (FISIP Universitas Bung Karno, 2023)
AbstractThe Tabuit ritual is a culture from the Middle East brought by people of Indian descent who are Shia believers. Over time, there was an agreement between nagari (adat) to adapt the Tabuik celebration to Minangkabau customs, so that it developed into a Pariaman cultural tradition. The main elements of tabuik, such as bungo salapan, tonggak atam, tonggak serak, jantuang-jantuang, pasu-pasu, and ula gerang which number eight are a description of the combination of Pariaman customs and religion. The traditional values contained in tabuik are not far from religious values. The research approach uses qualitative. While conceptual, namely the process of synthesis between Islam and Nusantara culture. With the synthesis process, the dynamics that occur in the Islamic culture of the archipelago continue to move dynamically and progressively by actualizing themselves in accordance with the context of their time.Keywords: Tabuik tradition, Islamic legacy, Pariaman local culture, synthesis process.